KOTAK SCOPOPHILIA VISUALISASI PROSES SUBLASI MEKANISME PERTAHANAN EGO - Nandang Gumelar Wahyudi (Jurusan Seni Rupa ISBI Bandung, 2021)
This work is a process of designing and creating three-dimensional works of art that rely on Sigmund Freud's Psychoanalysis as a grand theory, focusing on the sublation process of the Human Ego Defense Mechanism which is visualized through the Free Association method with various visual symbols produced from various media and mixed techniques (painting, drawing, collage, found objects, digital photos, lights, sound, assembling) which are placed in a number of boxes made of wood which are designed in such a way as a 'space' representation of the visual concept framework of Scopophilia. Departing from the theme of scopophilia and visual ideas placed within the framework of Freud's Psychoanalysis, the Scopophilia Box is expected to be a bridge for interpreting the spaces of erotic desire in the creative process carried out by the author as an art creator by placing it in the position of subject and object that cannot be tamed by language, law, morality or religion.Keywords: Scopophilia, Box, Sublimation, Ego Defense Mechanisms, Psychoanalysis.————————————————————————————-Karya ini merupakan proses perancangan dan penciptaan karya seni rupa tiga dimensi yang bersandar pada Psikoanalisa Sigmund Freud sebagai grand theory, berfokus pada proses sublasi dari Mekanisme Pertahanan Ego Manusia yang divisualisasikan melalui metode Asosiasi Bebas dengan berbagai simbol visual yang dihasilkan dari beragam media dan teknik campuran (painting, drawing, collage, benda temuan, foto digital, lampu, suara, assembling) yang diletakan dalam sejumlah kotak yang terbuat dari kayu yang dirancang sedemikian rupa sebagai ‘ruang’ representasi dari kerangka konsep visual Scopophilia. Berangkat dari tema scopophilia dan ide visual yang diletakkan dalam kerangka Psikoanalisa Freud, Kotak Scopophilia diharapkan menjadi sebuah jembatan tafsir ruang-ruang hasrat erotik dalam proses berkreasi yang dilakukan penulis sebagai kreator seni dengan menempatkannya pada posisi subyek sekaligus obyek yang tak bisa dijinakkan bahasa, hukum, moralitas atau agama. Kata Kunci: Scopophilia, Kotak, Sublasi, Mekanisme Pertahanan Ego, Psikoanalisa.